The Role of Intellectual Capital in Sustainability Performance - Inayati, Nur Isna; Pramono, Hadi; Rahmawati, Ika Yustina; Mustapha, Nur Diyana (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
The advancement of the global economy and technology has facilitated companies’ production processes while also enabling greater exploitation of natural resources. Ignoring the sustainability principles of profit, people, and planet (3P) leads to environmental degradation. Therefore, a strong commitment to sustainable practices is essential to safeguard economic, social, and environmental well-being for present and future generations. This responsibility is carried out through environmental, social, and governance (ESG) performance. ESG is important because it is not only with stakeholders but also related to investors. An important thing that can maintain and improve this commitment is having intellectual resources. Resource-based view theory and legitimacy theory are the basis for this study. The research sample was 32 energy sector companies with 115 data. Data analysis used EVIEWS because of the unbalanced data panel. This study shows that capital employed, structural, and human capital do not affect sustainability performance. In this study, the relational capital variable has a positive effect on sustainability performance. The intellectual capital variable measured by MVAIC does not affect sustainability performance.